A method to fabricate nanoscale gaps in graphene nano-constrictions by electrical breakdown - Oliver Schmuck; Davide Beretta; Roman Furrer; Jacopo Oswald; Michel Calame (AIP Advances, 2022)
This work reports on a method to open nanoscale gaps in h-shaped graphene nano-constrictions by electrical breakdown at room temperature and pressure below 10−5 mbar. The method was validated on 275 devices, fabricated on eight different chips, using Chemical Vapor Deposition (CVD)-grown graphene from in-house production and from two commercial sources. The gap width was estimated by fitting the I–V traces after electrical breakdown with the Simmons model for the intermediate-voltage range. The statistics on the collected data demonstrates that the method results in normally distributed nanoscale gaps in h-shaped graphene nano-constrictions, with an estimated average width centered around 1 nm and a gap fabrication yield of 95%.